Water content modifies the structural development of sodium metasilicate-activated slag binders - Bernal, S. A.; San Nicolas, R.; Van Deventer, J. S. J.; Provis, J. L. (Revista ALCONPAT, 2015)
The effect of modifying the water content of an alkali-activated slag binder was assessed, in terms of the kinetics of reaction and the structural development of the material. There is not a systematic correlation between the water content of the mix and the rate of reaction, indicating that there is an optimal value that favours dissolution of the slag and precipitation of reaction products. A higher water content reduced the crystallinity and density of the reaction products, especially at advanced age. Small changes in the water content can have a significant impact on the compressive strength development of alkali-silicate activated slag mortars, suggesting that when producing materials based on alkali-activated binders, it is essential to carefully control the water content.